Hantavirus: Structure, Mechanism of Transmission of Disease, Development of Drugs and Vaccines, and Prevention in Indonesia - Nur Sabiq Assadah; I Sendow; NLP I Dharmayanti (Indonesian Center for Animal Research and Development, 2020)
Hantavirus is a zoonosis transmitted by rodents and have been spread in various countries. Hantavirus causes Hantavirus Pulmonary Syndrome (HPS) and Haemorrhagic Fever with Renal Syndrome (HFRS) in humans is still receiving worldwide attention due to the high case fatality rate. Epidemiological studies have shown that Hantavirus is widespread globally, including in Indonesia. Indonesia is an archipelago and has a tropical climate, and is crossed by the equator so that it has an enormous diversity of animals, including those that become reservoirs of Hantavirus and other vulnerable animals. The high risk of developing Hantavirus in Indonesia does not rule out the possibility of a Hantavirus outbreak if no preventive action is taken. Until now there is no effective and safe vaccine or treatment for Hantavirus. Various development efforts continue to be made to obtain an appropriate and safe vaccine to prevent and stop the spread of Hantavirus. This paper discusses Hantavirus, including its structure and mechanism of transmission, the current situation of Hantavirus in Indonesia and the efforts that can be made to prevent Hantavirus, including the development of vaccines and their drugs.